2017
DOI: 10.1159/000485782
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Restriction Affects Feed Intake and Amino Acid Metabolism via Gut Microbiome in Piglets

Abstract: Background/Aims: Our previous reports suggested that dietary supplementation with lysine influenced intestinal absorption and metabolism of amino acids. In this study, we further investigated the effect of lysine restriction (30%) on feed intake and we also tested the hypothesis that gut microbiome contributed to the potential mechanism of lysine restriction-mediated feeding behavior. Here, we profiled gut microbial communities by sequencing 16S ribosomal ribonucleic acid (rRNA) genes from gut samples as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 39 publications
3
86
1
1
Order By: Relevance
“…Yin et al 53 reported that the two main phyla constituting the gut microbiota of mice were the Firmicutes and Bacteroidetes after supplementing high-fat and melatonin to the diet of mice. By contrast, Yin et al 54 reported that the Firmicutes and the Proteobacteria were the two main bacterial phyla in the gut microbial of piglets during dietary lysine restriction. Tannock 55 reported that the physiological and dietary factors were the key conditions that may influence the composition and abundance of the intestinal microbiota.…”
Section: Effects Of Dietary Pom Levels On Fecal Microbial Compositionmentioning
confidence: 88%
“…Yin et al 53 reported that the two main phyla constituting the gut microbiota of mice were the Firmicutes and Bacteroidetes after supplementing high-fat and melatonin to the diet of mice. By contrast, Yin et al 54 reported that the Firmicutes and the Proteobacteria were the two main bacterial phyla in the gut microbial of piglets during dietary lysine restriction. Tannock 55 reported that the physiological and dietary factors were the key conditions that may influence the composition and abundance of the intestinal microbiota.…”
Section: Effects Of Dietary Pom Levels On Fecal Microbial Compositionmentioning
confidence: 88%
“…For communities with identical species richness, an increased diversity is reflected by increased species uniformity. Microbial microecology in the intestine of mice is associated with the development of DSS-induced colitis [21,25,26]. Research has found that the compositions and varieties have changed in DSS-induced mouse models, such as those of Bacteroides, Lactobacilli, Parabacteroides, Enterobacteriaceae, and Anaerotruncus [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The results are presented in micromolar equivalents of ascorbic acid, an antioxidant normally found in the plasma [20]. Superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) kits supplied by the Jiancheng Bioengineering Institute, Nanjing, China, were used to evaluate the antioxidant enzyme activities, defined as the quantity of enzyme degrading 1 µmol of substrate per minute [21]. The results are presented in units per mg of protein.…”
Section: Serum Antioxidant Capacity and Antioxidant Enzymesmentioning
confidence: 99%
“…The PCR cycling condition was 40 cycles at 94°C for 40 seconds, 60°C for 30 seconds, and 72°C for 35 seconds. The relative expression was expressed as a ratio of the target gene to the control gene using the formula 2 −(∆∆Ct) , where ∆∆Ct = (Ct Target − Ct β‐actin ) treatment − (Ct Target − Ct β‐actin ) control . Relative expression was normalized and expressed as a ratio to the expression in the control group …”
Section: Methodsmentioning
confidence: 99%
“…Paired‐end sequencing was performed on the Illumina MiSeq platform, and a phylogenic tree and OTU table were obtained from the Mothur Bayesian classifier. Sequencing libraries were generated and analyzed according to our previous study . Principal coordinate analysis (PCoA) was performed to get principal coordinates and visualize from complex, multidimensional data.…”
Section: Methodsmentioning
confidence: 99%